Personal resources and depression in schizophrenia: The role of self-esteem, resilience and internalized stigma. (October 2017) - Rossi, Alessandro; Galderisi, Silvana; Rocca, Paola; Bertolino, Alessandro; Rucci, Paola; Gibertoni, Dino; Stratta, Paolo; Bucci, Paola; Mucci, Armida; Aguglia, Eugenio; Amodeo, Giovanni; Amore, Mario; et al.
Abstract: Depression in schizophrenia represents a challenge from a diagnostic, psychopathological and therapeutic perspective. The objective of this study is to test the hypothesis that resilience and self-stigma affect depression severity and to evaluate the strength of their relations in 921 patients with schizophrenia. A structural equation model was tested where depression is hypothesized as affected by resilience, internalized stigma, gender and negative symptoms, with the latter two variables used as exogenous covariates and the former two as mediators. The analysis reveals that low resilience, high negative symptoms, female gender were directly associated with depression severity, and internalized stigma acted only as a mediator between avolition and resilience, with similar magnitude. The cross-sectional study design and the variable selection limit the generalizability of the study results. The model supports a complex interaction between personal resources and negative symptoms in predicting depression in schizophrenia. The clinical implication of these findings is that personal resources could be a significant target of psychosocial treatments. Highlights: A structural equation model between depression and psychological resources is shown. The model underlines the interaction of several types of variables. The nature of these variables may add cues for psychosocial treatment.